Determinants of Tax Evasion in Food and Beverage Manufacturing Companies: A Fraud Pentagon Perspective - Nurfilaili Diah Pitalokasari; Ahmad Dahlan; Yeni Tata Rini; Mitha Endah Aprilia (Research Horizon, 2026)
Tax evasion remains a major concern because it reduces state revenue and weakens public trust in the taxation system, particularly in manufacturing companies with high fraud risk exposure. Therefore, this study aims to analyze the influence of Fraud Pentagon Theory, consisting of pressure, opportunity, rationalization, competence, and arrogance, on tax evasion indications in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employs a quantitative descriptive approach using secondary data obtained from audited financial statements and annual reports. The sample consists of 43 companies selected through purposive sampling, resulting in 172 observations. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis with SPSS. The findings reveal that pressure, opportunity, and rationalization significantly influence tax evasion, while competence and arrogance do not show significant effects. Pressure, proxied by return on assets, is identified as the most dominant factor affecting tax evasion practices. These results imply that financial pressure and weak supervisory mechanisms can encourage companies to engage in tax-related fraud. Therefore, strengthening internal control systems and corporate governance is essential to reduce tax evasion risks.